Photoperiod Effect on Growth and Survival Rate of Baung Fish (Hemibagrus nemurus) Larvae - Hajjar Falida Putri Kurnia; Sukendi Sukendi; Nuraini Nuraini (Jurnal Akuakultur SEBATIN, 2022)
This purpose of this study to determine the effect of different photoperiods on the growth and survival of baung fish larvae. This research was conducted from May 2021 to August 2021 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine sciences, Riau University, Pekanbaru. The method used in this study is an experimental method using a completely randomized design (CRD) one factor five treatment levels and three replications. The treatments used were as follows P1 (24 hours dark), P2 (24 hours light), P3 (12 hours dark, 12 hours light), P4 (18 hours dark, 6 hours light), P5 (6 hours dark, 18 hours). The baung fish (Hemibagrus mumurus) is a nocturnal fish. The photopriode will affect baung fish larvae in fish activities such as eating habits and behavior. The results showed that the best absolute weight, absolute length, daily growth rate, and survival rate were obtained in P1 treatment, which was 24 hours dark with an absolute absolute weight of 3.22 g, an absolute length of 5.59 cm, a daily growth rate of 12.74. % , and 92% passability